Functional Genomic Screening Independently Identifies CUL3 as a Mediator of Vemurafenib Resistance via Src-Rac1 Signaling Axis - Vanneste, Marion; Feddersen, Charlotte R.; Varzavand, Afshin; Zhu, Elliot Y.; Foley, Tyler; Zhao, Lei; Holt, Kathleen H.; Milhem, Mohammed; Piper, Robert; Stipp, Christopher S.; Dupuy, Adam J.; Henry, Michael D. (Frontiers in Oncology, 2020)
Patients with malignant melanoma have a five‐year survival rate of only 15–20% once the tumor has metastasized to distant tissues. While MAP kinase pathway inhibitors (MAPKi) are initially effective for the majority of patients with melanoma harboring BRAFV600E mutation, over 90% of patients relapse within two years. Thus, there is a critical need for understanding MAPKi resistance mechanisms. In this manuscript, we performed a forward genetic screen using a whole genome shRNA library to identify negative regulators of vemurafenib resistance. We identified loss of NF1 and CUL3 as drivers of vemurafenib resistance. NF1 is a known driver of vemurafenib resistance in melanoma through its action as a negative regulator of RAS. However, the mechanism by which CUL3, a key protein in E3 ubiquitin ligase complexes, is involved in vemurafenib resistance was unknown. We found that loss of CUL3 was associated with an increase in RAC1 activity and MEKS298 phosphorylation. However, the addition of the Src family inhibitor saracatinib prevented resistance to vemurafenib in CUL3KD cells and reversed RAC1 activation. This finding suggests that inhibition of the Src family suppresses MAPKi resistance in CUL3KD cells by inactivation of RAC1. Our results also indicated that the loss of CUL3 does not promote the activation of RAC1 through stabilization, suggesting that CUL3 is involved in the stability of upstream regulators of RAC1. Collectively, our study identifies the loss of CUL3 as a driver of MAPKi resistance through activation of RAC1 and demonstrates that inhibition of the Src family can suppress the MAPKi resistance phenotype in CUL3KD cells by inactivating RAC1 protein.